التاريخ السياسي لمسقط وعمان في الفترة ما بين 1308-1339هـ/1891-1960م - الحييد, عبد الله بن حامد (جامعة أم القرى, 1991)
Keywords: Vie politique -- Oman -- 1888–1913; Vie politique -- Oman -- 1913-1932; Vie politique -- Oman -- 1932-1970

Imam Salim b. Rashid and the Imamate revival in Oman 1331/1913-1338/1920 - Hāshimī, Saʿīd b. Muḥammad b. Saʿīd al- (University of Leeds, 1994)
The principal aim of this thesis is to assess the performance of Imam Salim b.Rashid and the Imamate revival in Oman during the second decade of the 20th century. It presents biographical information about Imam Salim, with special reference to the military and political policies by which he established and consolided his Imamate in the Interior Province, and his relations with the Sultan and the latter's British supporters. An attempt is also made to explore the relationship between the Imam and the Omani tribes and to evaluate his administrative success. This thesis comprises eight chapters, and the introduction and conclusion. The introduction reviews the relevant literature on the topic. The first chapter describes the geographical setting and provides a historical background, relating to three principal matters: the rise of the Iba<;liyyah and the development of the Imamate in Oman; the events in Oman after Sd. Sa'id's death up to 1913; and the effects of the First World War. The second chapter seeks to give an account of the career of Imam Salim's life and the Imamate revival. The third chapter discusses the manner in which the Imam was elected, private and public allegiance (bay'ah) and the Imam's aims and policy programme. Chapter Four deals with the Imam's military operations and the spread of his authority over Oman. Chapter Five examines the attempts at negotiation between the Imam and the Sultan, and the role of the British Government and the local figures in this regard. Chapter Six is devoted to a discussion of the role of the tribes in support of Imam Salim, and the extent of the Imam's influence over these tribes. Chapter Seven assesses the Imam's administrative machinery, including the political system, the bureaucracy, education policy, and financial apparatus. Chapter Eight examines the causes behind the assassination of Imam Salim and the signing of the Treaty of al-Sib. In the conclusion, we present the findings of the research as they have emerged from the assessment of the course of events in Oman. We have said that the Omanis succeeded in reviving the Imamate and elected Imam Salim al-KharU~i who devoted his efforts to establish the foundations of the state, and peace prevailed in the country after the treaty of al-Sib in 1920.
Keywords: Vie politique -- Oman -- 1913-1932

Oman under Sultans Taimur and Sa'īd, 1913-1970 - Wuhaibi, Abdullah Muhammad Fahad al- (University of Cambridge, 1995)
Keywords: Vie politique -- Oman -- 1913-1932; Vie politique -- Oman -- 1932-1970